Analysis of Problem Financing Settlement in Murabahah Agreements with DSN MUI Fatwa: (Case Study at BPRS HIK Parahyangan Cileunyi Branch) - Hakim, Arifin Rahman; Badrusarif, Arif; Wibawa, Ginan (Sharia Business Management Department of STEBIS Bina Mandiri, 2024)
This research aims to examine the resolution of financing problems in murabahah contracts by referring to the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). This study focuses on PT BPRS HIK Parahyangan Cileunyi Branch as a case study. The background underlying this research includes the history of Islamic banking, the basic principles of sharia banking, as well as the phenomenon of problematic financing in the context of sharia banks. Problem identification focuses on the factors that cause financing problems, the form of resolution applied, and the conformity of practices with the DSN-MUI fatwa. By limiting the discussion to the concept and implementation of resolving problematic financing in murabahah contracts, this research obtains a descriptive-analytical problem formulation. The research methodology used is a qualitative approach with data collection techniques through semi-structured interviews. The results of this research are expected to provide a comprehensive picture regarding the resolution of problematic financing in murabahah contracts, as well as its conformity with the DSN-MUI fatwa, so that it can contribute to the development of knowledge in the field of sharia economic law and provide practical recommendations for related parties in the sharia banking industry.